Hybrid monitoring systems for global processes. The results of the experiment at the first point of the hybrid system - Sarian, V. K.; Mkrtchyan, A. R.; Ermakov, V. V.; Nazarenko, A. P.; Lyubushin, A.; Meshcheryakov, R. V.
This article is a continuation of the topic with which Sarian V.K. and A.R. Mkrtchyan [7] spoke at «International Conference on Electron, Positron, Neutron and X–Ray Scattering under External Influences & International School named after G. A. Askaryan 16–22 October 2017» «Invitation to the use of a powerful experimental ground created in the Russian Federation for monitoring the global processes based on new information technologies». The first point of the hybrid network was organized at the beginning of 2018 with the participation of scientists and specialists of the Federal State Unitary Enterprise NIIR, GEOKHI RAS, IPE RAS, IAPP NAS RA, ICS RAS and others at the field national center for complex environmental and biogeochemical studies of the GEOHI RAS, which is located on a geological base Moscow State University in the village N. Unal of North Ossetia (RF). The report will describe the measuring equipment used and discuss the significance of the results of measurements for short-term, medium-term and long-term forecasts of global processes, including emergency situations. The experiments will be continued from 2020 to 2021. It is planned to expand the experiment in potentially seismic areas in Kamchatka and Armenia. Similar experiments will be conducted at national training sites in the countries of the Asia-Pacific region in accordance with the decision of the 58th meeting of the Working Group on Telecommunications and Information in the framework of the Asia-Pacific Economic Cooperation (APEC), which was held at the end of 2018 in Taipei (Chinese Taiwan). Similar experiments will be carried out at national training sites in the countries of the Asia-Pacific region in accordance with the decision of the 58th meeting of the Working Group on Telecommunications and Information in the framework of the Asia-Pacific Economic Cooperation (APEC), which was held at the end of 2018 in Taipei (Chinese Taiwan). At this meeting, the authors made keynote speeches. In the future, on this basis, it is planned to establish an international interdisciplinary collaboration of scientists and specialists on the formulation of development goals and regulations on the use of the created global hybrid monitoring system for global processes of natural and technogenic origin.
Keywords: Physics; Cross-Disciplinary